2019
DOI: 10.1021/acsami.9b10398
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Multisite Trielement Ru–Ni–Fe Alloy Nanocatalysts with Efficient and Durable Catalytic Hydrogenation Performances

Abstract: The co-decomposition of non-noble metals into Ru nanoparticles (NPs) would provide multiple active centers as well as synergistically alter the reaction pathway, enhancing the catalytic hydrogenation performance. Herein, a facile route for synthesizing trielement Ru–Ni–Fe alloy NPs was proposed. The catalytic hydrogenation performance of NPs was measured using p-nitrophenol as a model. The synergistic effect of these three elements (Ru, Ni, and Fe) and synergistic catalysis of multiple crystal faces greatly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Ru atoms appeared not only in the center of NPs but also on the NP surface. Besides the sharp absorption peak at 270 nm of Ru NPs, a broad absorption cross section was also shown by AuRu NPs from 520 to 600 nm (Figure g), due to the LSPR properties of Au components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ru atoms appeared not only in the center of NPs but also on the NP surface. Besides the sharp absorption peak at 270 nm of Ru NPs, a broad absorption cross section was also shown by AuRu NPs from 520 to 600 nm (Figure g), due to the LSPR properties of Au components.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmon-resonant excitation of plasmonic nanomaterials is expected to trigger the generation of a high concentration of energy carriers. Platinum group metals (such as Pt, Ru, Pd, and Ir) with a high electronic density of states have been shown to exhibit exceptional electrocatalytic properties. In particular, Ru NPs and their composite materials with controlled sizes and morphologies have shown remarkable catalytic hydrogenation performances. , However, to date, no studies have been reported for the plasmon-enhanced electroactivity of Ru NPs. There have been few studies on the electroactivity performances of Ru NPs under irradiation and the composites of Ru NPs and plasmonic NPs, and the mechanism underlying the electroactivity of these materials remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Inspired by the excellent activity of Ru 0.013 @NC f for anodic HER, we additionally investigated its catalytic activity toward ANR in a model system containing p-nitrophenol (p-NP) and sodium borohydride (NaBH 4 ) at room temperature. As suggested by the control experiment and literature report, [28] p-NP cannot be hydrogenated or reduced by using NaBH 4 alone. Nevertheless, after adding Ru 0.013 @NC f as catalyst, the yellow color of the p-NP/NaBH 4 mixture quickly faded.…”
Section: Aromatic Nitroreduction Activitymentioning
confidence: 68%
“…(ANRs). [26][27][28] Nevertheless, advanced catalyst design still remains challenging. First, many of Ru-based nanostructures may suffer from serious aggregation during catalysis and hence exhibit poor durability.…”
Section: Introductionmentioning
confidence: 99%